Palladium Nanoparticles Immobilized on Poly(vinyl chloride)-Supported Pyridinium as an Efficient and Recyclable Catalyst for Suzuki-Miyaura Cross-Coupling Reaction - Bo Zhou; Yi-Qun Li (E-Journal of Chemistry)
The palladium nanoparticles immobilized on the polymeric surface of poly(vinyl chloride)-supported pyridinium (PVC-Py-Pd0) were achieved by a simple procedure by applying the corresponding functionalized polymer and palladium chloride in ethanol solution. The as-prepared catalyst (PVC-Py-Pd0) was found to be air and moisture stable and exhibits significant catalytic activity for Suzuki-Miyaura cross-coupling reaction of various aryl halides and phenylboronic acid under milder operating conditions. The procedure presented here showed several merits such as short reaction time, simple experimental and isolated procedure and excellent yields of products. Furthermore, the catalyst can be easily recovered and reused for at least six times with consistent activities.